Ammonoids, their biozonation and their palaeobiogeographic relation across the Turonian-Coniacian boundary in northern Coahuila, Mexico - Ifrim, Christina; Porras Múzquiz, Héctor; Stinnesbeck, Wolfgang (Cretaceous research, 2019)
The Rosario section in northern Coahuila, northeastern Mexico, contains a complete record of distal shelf deposits across the Turonian-Coniacian boundary. Here we describe the ammonoids, the biozonation based on these cephalopods, their taphonomy and some palaeobiogeographic relations. Gaudryceras mite, Peroniceras (P.) tridorsatum, P. (P.) dravidicum, Forresteria (F.) alluaudi, F. (F.) brancoi, F. (F.) peruana, Baculites sweetgrassensis, B. yokoyamai, Neocrioceras maximum, Schlueterella stinnesbecki, Scaphites (S.) frontierensis, S. (S.) preventricosus, S. (S.) sagensis, and S. (S.) uintensis were identified at El Rosario and a nearby complementary outcrop at Carranza. The lower Coniacian Scaphites preventricosus, F. (F.) alluaudi, P. (P.) dravidicum and Neocrioceras maximum zones are represented and provide correlation with sections of the US Western Interior and Europe. The original index for the base of the Coniacian, F. (F.) peruana is also present, although few data exist below the Turonian-Coniacian boundary level. The ammonoids were not transported far before deposition, indicated by their preservation and size distribution. A moderate diversification in open-coiled diplomoceratids seemed to have started in the early Coniacian in this region. The El Rosario section provides a detailed ammonoid record and biozonation, and it is one of very few sections in the world where it can be correlated with the standard inoceramid biozonation.
Gesehen am 22.10.2019